Effect of Intrinsic Point Defect on the Magnetic Properties of ZnO Nanowire - Jiangni Yun; Zhiyong Zhang; Tieen Yin (The Scientific World Journal)
The effect of intrinsic point defect on the magnetic properties of ZnO nanowire is investigated by the first-principles calculation based on the density functional theory (DFT). The calculated results reveal that the pure ZnO nanowire without intrinsic point defect is nonmagnetic and ZnO nanowire with VO, Zni, Oi, OZn, or ZnO point defect also is nonmagnetic. However, a strong spin splitting phenomenon is observed in ZnO nanowire with VZn defect sitting on the surface site. The Mulliken population analysis reveals that the oxygen atoms which are close to the VZn defect do major contribution to the magnetic moment. Partial density states calculation further suggests that the appearance of the half-metallic ferromagnetism in ZnO nanorod with VZn originates from the hybridization of the O2p states with Zn 3d states.